Enhancing neuroprotective effect of aminosalicylic acid-grafted chitosan electrospun fibers for spinal cord injury. (February 2023) - Wang, Dahao; Zhao, Haosen; Xu, Chang; Lin, Sen; Guo, Yue
Abstract: The hyperinflammation microenvironment after spinal cord injury (SCI) remains a great challenge for neural regeneration. Methylprednisolone has been used to reduce the inflammatory response after SCI, but it is controversial due to side effects associated with off-specific targeting effects. In this study, we synthesized in situ 5-ASA grafted chitosan electrospun fibers (ASA-EF) with excellent injectable and self-healing properties to reprogram nerve cells via displaying biological distribution, gene expression, and functional changes. With the support of ASA-EF, the downregulation of inflammatory cytokines expression and the upregulation of anti-inflammatory and regenerative gene expression were found in vitro studies. Moreover, ASA-EF administration polarized macrophages toward proregenerative phenotypes in the injured lesion, and significantly reduced cavity area. In addition, ASA-EF administration increased myelination and regenerating axons and improved motor function (score of 5 versus 2 for SCI group). These results illustrate that the neuroprotective effect of this artificial nanoplatform will facilitate the clinical treatment of traumatic-related diseases via forming a recycled microenvironment that supports regeneration and functional recovery. These particles may be applied to trauma and potential other inflammatory diseases. Graphical abstract: Image 1 Highlights: Electrospun fibers (EF) are formed without an active pharmaceutical ingredient that can have offtarget effects in injured spinal cord. Following ASA-EF injection, immune cell infiltration is reduced, correlating with decreased tissue degeneration after SCI. ASA-EF developed into a permissive microenvironment characterized by proregenerative immune cell phenotypes, expression of regeneration associated genes, increased axons and myelination, and a substantially improved functional recovery.